(untitled) (Tumou Tou: Jurnal Pengabdian Masyarakat, 2025)
In Indonesia, dental and oral diseases, especially dental caries and periodontal disease, are still widely suffered, both by children and adults. The purpose of this activity is to provide knowledge so that they can see the signs of tooth decay. Providing knowledge so that diabetes mellitus can be prevented as early as possible. Education to the school health unit cadres, teachers and students about how to detect early, then teachers together with the community service team teach students and conduct demonstrations on how to detect caries early. With the implementation of community service activities, dental health problems (fissure) of students at school can be overcome and prevented from continuing so that dental caries or cavities do not occur by 61.31%. Efforts to prevent dental caries with the Fissure Sealant program are one of the primary prevention methods carried out to prevent dental caries.